Enduring Motives : The Archaeology of Tradition and Religion in Native America - DeBoer, Warren R.; Sundstrom, Linea (Book collections on Project MUSE., 2012)
Enduring Motives examines tradition and religious beliefs as they are expressed in landscape, the built environment, visual symbols, stories, and ritual. Bringing together archaeologists and Native American experts, this volume focuses on long-lived religious traditions of the native peoples of the Americas and how religion codifies, justifies, and reinforces these traditions by placing a high value on continuity of beliefs and practice. Using clues from the archaeological record to piece together the oldest religions of the Americas, Enduring Motives is organized into four parts.